Diversification of Hox Gene Clusters in Osteoglossomorph Fish in Comparison to Other Teleosts and the Spotted Gar Outgroup. Issue 7 (23rd February 2017) - Martin, Kyle J; Holland, Peter W H
ABSTRACT: An ancient genome duplication (TGD or 3R) occurred in teleost fish after divergence from the lineage leading to gar. This genome duplication is shared by the three extant teleost lineages: Osteoglossomorpha (bony‐tongues), Elopomorpha (eels and tarpons), and Clupeocephala (a large clade including salmon, carp, medaka, zebrafish, cichlids, pufferfish, stickleback, and ∼26, 000 other species). After TGD, different clupeocephalan species retained different gene duplicates; this is seen clearly in Hox gene clusters but extends to all genes. Since divergent resolution of TGD paralogs is a potential driving force for speciation, it is possible this contributed to diversification of this clade. The extent to which divergent resolution of TGD paralogs occurred within Osteoglossomorpha has not been investigated in detail, and Hox cluster organization has been reported for just two species: Pantodon buchholzi (Pantodontidae) and Scleropages formosus (Osteoglossidae). We applied survey‐scale genome sequencing and de novo assembly to three further osteoglossomorph taxa: Osteoglossum bicirrhosum (Osteoglossidae), Chitala ornata (Notopteridae), and Gnathonemus petersii (Mormyridae). We find that each retained more Hox genes than clupeocephalan taxa (excluding those that underwent additional genome duplication), but fewer than eels. Several Hox genes are missing in all teleosts, including duplicates of two Hox genes present in the slow evolving pre‐TGD genome of the spotted gar. We find divergent resolution through individual gene losses, and whole cluster losses have been rampant across osteoglossomorphs, despite their extant species paucity. We suggest that reciprocal gene loss following TGD was probably insufficient to drive the exceptional diversification of teleosts. GRAPHICAL ABSTRACT: Genomic sequencing of three osteoglossomorph fish reveals diversity in their Hox gene complements and radical differences to the previously studied Pantodon, indicating numerous independent gene losses and gene cluster losses after genome duplication. Variability is also seen in other teleost fish and contrasts with the slow‐evolving genome of the spotted gar.